Healthcare Providers՚ Experience of Non-Linguistic Barriers to Healthcare Provision for Official Language Illiterate Patients in Far-North Cameroon Healthcare Centers: A Contribution to Intercultural Communication - Kamtchueng, Lozzi Martial Meutem (CV. Global Health Science Group, 2024)
Non-linguistic barriers have significant impacts on healthcare provisions. Drawing data from questionnaires administered through simple random sampling to 487 healthcare providers in 45 healthcare centers of the Far-North region of Cameroon, this paper sets out to study healthcare providers՚ experience of non-linguistic barriers to healthcare provision for official language illiterate patients (i.e. patients who lack complete communicative skills in official languages of Cameroon (English and French)). More precisely, the work investigates non-linguistic barriers to healthcare provision in Far-North Cameroon healthcare centers and discusses some remedial strategies. Campinha-Bacote՚s (2002) Cultural Competence of Healthcare Delivery has served as the theoretical framework for the study and the approach of analysis is both quantitative and qualitative. Findings reveal that religious barriers; cultural beliefs, practices, taboos and witchcraft; overdependence on traditional medicine, traditional doctors and soothsayers and exacerbated patriarchy constitute serious hindrance to healthcare provision in the healthcare centers in this region of Cameroon. Current trends and suggestions to limit these barriers include the following: informing, educating, communicating and counselling; familiarization of healthcare providers to the cultural practices of the community; gender-sensitiveness with regard to the caring of patients; referring some patients to colleagues of other healthcare centers; priority to female healthcare providers in women health services; recruiting healthcare providers who are of the locality in which healthcare centers are found and getting substitute product for blood during blood transfusion. It is argued that in addition to these current strategies, a more efficient approach to limit these barriers should incorporate intercultural competence. The paper intents to contribute to the domain of intercultural communication in the context of healthcare provision for official language illiterate patients in multicultural contexts.